2015
DOI: 10.1021/acs.energyfuels.5b00953
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Particle Shrinkage and Devolatilization Models on High-Temperature Biomass Pyrolysis and Gasification

Abstract: The effects of two different particle shrinkage and devolatilization models on biomass pyrolysis and gasification behavior in a high-temperature (1400°C) entrained-flow reactor have been studied employing a three-dimensional Eulerian− Lagrangian computational fluid dynamic model in the framework of open-source codes, OpenFOAM. Both qualitative results (temperature distribution, gas composition, and particle distribution) and quantitative results (pyrolysis time, syngas production, carbon conversion, and partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Instead of only studying temperature, Chaos also performed the sensitivity analyses of mass loss rate (MLR) to material properties. Other studies on the sensitivity of the pyrolysis model regarding different parameters had been conducted by researchers in the past as well . In this study, sensitivity analyses were performed on both the surface temperature and the MLR for a charring material to quantify the sensitive of the input properties.…”
Section: Methodsmentioning
confidence: 99%
“…Instead of only studying temperature, Chaos also performed the sensitivity analyses of mass loss rate (MLR) to material properties. Other studies on the sensitivity of the pyrolysis model regarding different parameters had been conducted by researchers in the past as well . In this study, sensitivity analyses were performed on both the surface temperature and the MLR for a charring material to quantify the sensitive of the input properties.…”
Section: Methodsmentioning
confidence: 99%
“…It was found higher temperature leads to lower tar yield. The effects of particle shrinkage were studied by testing two shrinking models in the DPM simulation of biomass pyrolysis in a falling reactor 98 with Scheme A2. The results showed that the constant volume model predicts a faster pyrolysis and longer particle residence time than the constant density model.…”
Section: Reactor-scale Biomass Pyrolysismentioning
confidence: 99%
“…As mentioned before, the particle shrinkage should be considered in the modeling of conversions of solid fuels. A pair of shrinkage models were most commonly adopted in previous numerical studies: , namely, the constant size model and constant density model. Other shrinkage patterns were also proposed or employed by researchers. , Among different particle shrinkage models, the model proposed by Di Blasi gives a comprehensive description of the particle shrinkage for biomass pyrolysis process.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before, the particle shrinkage should be considered in the modeling of conversions of solid fuels. A pair of shrinkage models were most commonly adopted in previous numerical studies: 19,20 namely, the constant size model and constant density model. Other shrinkage patterns were also proposed or employed by researchers.…”
Section: Introductionmentioning
confidence: 99%